2021
DOI: 10.3390/cancers13153749
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Liposomal Chemotherapies to Treat Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancers (TNBCs) are highly aggressive and recurrent. Standard cytotoxic chemotherapies are currently the main treatment options, but their clinical efficacies are limited and patients usually suffer from severe side effects. The goal of this study was to develop and evaluate targeted liposomes-delivered combined chemotherapies to treat TNBCs. Specifically, the IC50 values of the microtubule polymerization inhibitor mertansine (DM1), mitotic spindle assembly defecting taxane (paclitaxel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…The relevant literature, in addition to [36,37,43,44,57] this study, revealed high expression of the surface receptors EGFR and CD47 in TNBC patient tissues. This study constructed an EGFR/CD47 dual-targeted mAb-EV to deliver the natural compound Ver-A for TNBC treatment.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…The relevant literature, in addition to [36,37,43,44,57] this study, revealed high expression of the surface receptors EGFR and CD47 in TNBC patient tissues. This study constructed an EGFR/CD47 dual-targeted mAb-EV to deliver the natural compound Ver-A for TNBC treatment.…”
Section: Resultssupporting
confidence: 50%
“…The TNBC PDX xenograft donor mice were purchased from The Jackson Laboratory and maintained at low passages of 2-4 in host NSG mice following our established protocol [57]. Briefly, either fresh harvested tumor or fresh frozen tumor tissues were minced into small fragments (<1 mm 3 ) and subcutaneously (s.c.) injected into the right flank of NSG mouse.…”
Section: Tnbc Patient-derived Xenograft (Pdx) Models and In Vivo Trea...mentioning
confidence: 99%
“…The transfected HKE 293AAV cells were harvested and centrifuged at 48-60 h for further AAV clarification. 3) Cationic liposomes transfection: We synthesized cationic liposomes following similar synthetic procedure of neutral liposomes (Si et al, 2021) with modifications: mixing 7 µmole 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), 7 µmole 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP) and 10 ml of chloroform and evaporating at 60 °C and 50 rpm for 1 h. The generated liposomes were analyzed using NanoSight, which showed concentration of 3.2 × 10 11 particles/ml and mean size of 92.6 ± 0.4 nm. Total of 30 µg three plasmids (10 µg each plasmid) were mixed with 900 µL of cationic liposomes, incubated on ice for 30 min, and mixed with Opti-MEM medium with volume ratio of 1:1.…”
Section: Adeno-associated Viruses Production Using Adherent Culturementioning
confidence: 99%
“…The brain GBM tissue arrays, including 35 cases and 70 cores, were purchased from US Biomax (Derwood, MD, USA). IHC staining was performed to identify the surface receptor in patient tissues as we described before [ 40 , 48 ]. The TMA slides were stained with rabbit anti-human EGFR mAb (Abcam, Waltham, MA, USA) and counterstained with hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…The sections of major organs harvested from the in vivo treatment with mAb-EV-Ver-A were stained with H&E. The detailed staining procedure has been reported in our previous publications [ 40 , 48 ].…”
Section: Methodsmentioning
confidence: 99%